Pendidikan Islam Sebagai Institusi Politik Demokrasi Tertinggi di Indonesia: Islamic Education as the Highest Democratic Political Institution in Indonesia - Mustofa, Imron (Halaqa: Islamic Education Journal, 2017)
The relationship and Islam democracy in Indonesia has been a topic. The possibility of Islam education is worth taking into account in the arena of Indonesian politics? How is Islamic education position in the world Indonesian government? Until that the Islamic education system plays in the world of Indonesian politics. To answers to the problems that this article is present. After through the review process, the article has finally found the conclusion that Indonesian democracy, its central idea of sovereignty in the hands of the people, has indirectly opened up Muslim opportunities form a democracy religious. That is, a system and elements Islamic foundations efforts to develop a religious model of Islamic education. This is due the peculiar nature of Islamic education which strongly emphasizes the importance of integral attitudes (tawhīdī) at all kinds of reality. Therefore, the government of Indonesia in the future, all started from Islamic education at this time. Because, the young people who is currently still a role as a student of this State of Indonesia journey.